Women and Terrorism; Analysis of the Repatriation Policy for the Wives and Children of Former Indonesian Citizens from ISIS - Shodiq, Shubhan (IAIN Bone, 2023)
The defeat of ISIS in 2019 still causes polemic. The polemic that occurred was the repatriation of sympathizers to their countries. In response to this problem, countries take different policies. Indonesia takes a policy of not repatriating its citizens. This decision has pros and cons in society. This paper examines the policy from the perspective of fiqh and human rights. This research is qualitative research. The approach used is the fiqh and human rights approach. The result of the study view that the government needs to review the policy. Furthermore, the author proposes that repatriation be carried out by assessment (especially for women and children), deradicalization program after returning home and punishment in accordance with statutory regulations.